2014
DOI: 10.1074/jbc.m114.567818
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation-mediated Repression of miR-941 Enhances Lysine (K)-specific Demethylase 6B Expression in Hepatoma Cells

Abstract: Background: Recent research has uncovered tumor suppressive and oncogenic potential of miRNAs. Results: miR-941 expression is regulated by DNA methylation, and is an important regulator of cell proliferation, migration, and invasion by directly targeting KDM6B in hepatocellular carcinoma (HCC). Conclusion: miR-941 may play an important role in suppressing tumor growth and metastasis in HCC. Significance: miR-941 may provide a potential biomarker for the diagnosis and treatment of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 49 publications
(43 reference statements)
2
31
1
Order By: Relevance
“…Furthermore, KDM6B gene expression was down-regulated with excess SAH, suggesting that a feedback mechanism may be triggered due to lack of substrate. Interestingly, it was recently reported in cancer cell lines that JMJD3 suppression can be mediated by miR-941, which is upregulated with DNA hypomethylation [56]. Similarly, EZH2 expression has been shown to be suppressed by microRNAs that may normally be transcriptionally repressed by DNA methylation [57].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KDM6B gene expression was down-regulated with excess SAH, suggesting that a feedback mechanism may be triggered due to lack of substrate. Interestingly, it was recently reported in cancer cell lines that JMJD3 suppression can be mediated by miR-941, which is upregulated with DNA hypomethylation [56]. Similarly, EZH2 expression has been shown to be suppressed by microRNAs that may normally be transcriptionally repressed by DNA methylation [57].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, miRNAs which act as tumor-suppressor genes and oncogenes are also subjected to regulation of epigenetics, such as DNA methylation status of promoter gene [10,17,12]. Various oncogenic or tumor-suppressor miRNAs are now known to be regulated via DNA methylation status of the miRNA promoter region [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, overexpression of JMJD3 in glioblastoma stem cells attenuates their proliferation by activating the p53 pathway (27), suggesting its antitumorigenic roles. By contrast, JMJD3 promotes T-ALL and hepatoma growth by enhancing their proliferation (22,23). However, the role of JMJD3 in the context of melanoma progression and metastasis remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have suggested that JMJD3 plays both tumorsuppressive and -promoting roles in a tumor type-specific manner (22)(23)(24)(25)(26)(27)(28). For example, oncogene-induced expression of JMJD3 in fibroblasts causes senescence by stimulating expression of tumor suppressors, including p14 ARF and p16 INK4A (25,26).…”
Section: Introductionmentioning
confidence: 99%